2014
DOI: 10.1007/s00436-013-3743-2
|View full text |Cite
|
Sign up to set email alerts
|

A penta-substituted pyridine alkaloid from the rhizome of Jatropha elliptica (Pohl) Muell. Arg. is active against Schistosoma mansoni and Biomphalaria glabrata

Abstract: Jatropha elliptica is a shrub distributed throughout the north and west of Brazil and reputedly possesses a wide range of therapeutical properties. The roots of this plant possess molluscicidal activity and contain terpenoids, coumarin, lignoid, steroids and alkaloid. In the present study, we assessed the schistosomicidal, miracicidal and cercaricidal activities (against Schistosoma mansoni) and molluscicidal activities (against adults and egg masses of Biomphalaria glabrata) of the alkaloid diethyl 4-phenyl-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 34 publications
2
31
0
1
Order By: Relevance
“…Based on LC 50 values, we found that psilostachyin and psilostachyin B were the main bioactive compounds responsible for the molluscicidal activity of A. artemisiifolia , with LC 50 values of 27.0 and 15.9 mg/L, respectively. Both psilostachyin and psilostachyin B also have molluscicidal activity against the snail Oncomelania hupensis , with mortality of 73.3 and 50% following exposure to 100 mg/L . These data, combined with the toxicity to GAS, indicate that psilostachyin and psilostachyin B have a broad spectrum of molluscicidal activity and that GAS appears to be more sensitive than O. hupensis .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Based on LC 50 values, we found that psilostachyin and psilostachyin B were the main bioactive compounds responsible for the molluscicidal activity of A. artemisiifolia , with LC 50 values of 27.0 and 15.9 mg/L, respectively. Both psilostachyin and psilostachyin B also have molluscicidal activity against the snail Oncomelania hupensis , with mortality of 73.3 and 50% following exposure to 100 mg/L . These data, combined with the toxicity to GAS, indicate that psilostachyin and psilostachyin B have a broad spectrum of molluscicidal activity and that GAS appears to be more sensitive than O. hupensis .…”
Section: Discussionmentioning
confidence: 86%
“…Sesquiterpene lactones and thiophenes have been found to be the bioactive compounds responsible for the molluscicidal activity of Ambrosia plants . In addition, many plant species have been found to have potential value as molluscicides for controlling GAS, such as Chenopodium quinoa , Pueraria peduncularis , Jatropha elliptica , Mikania micrantha , and Wedelia trilobat . A few saponins and alkaloids have been identified as the effective active components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other perennial plants, full grown J. curcas has main stem, branch and leaves. These aerial parts contain organic acids (Devappa et al, 2010;Aiyelaagbe et al, 2011), amyrin in stem bark (Misra and Misra, 2010;Islam et al, 2011), terpenes in leaves (Boateng and Kusi, 2008;Jummai and Okoli, 2014), curcins in latex (dos Santos et al, 2014;Falodun et al, 2014), phorbolesters in seeds (Agarwal et al, 2013;Bashir et al, 2013), saponins in kernel (Gámez-Meza et al, 2013;Pasha et al, 2013;Sharath et al, 2014), and sitosterol in roots (Abdelgadir and Van Staden, 2013;Khalil et al, 2013). Phytochemicals found in J. curcas can be explored for bio-prospecting new and novel bioactive compounds.…”
Section: Bioactive Compounds From Jatropha Curcasmentioning
confidence: 99%
“…Less attention has been paid to the other active constituents of Jatropha curcas L. seeds, such as polysaccharides [11], flavones [12], phytosterol [13], anthocyanin [14], and alkaloids [15]. Additionally, while Jatropha oil is the main product, the process of extracting and isolating the other active constituents from Jatropha curcas L. seeds has not been completely explored.…”
Section: Introductionmentioning
confidence: 99%